Age‐Related Changes in the Mechanical Regulation of Bone Healing Are Explained by Altered Cellular Mechanoresponse. (29th July 2019) - Borgiani, Edoardo; Figge, Christine; Kruck, Bettina; Willie, Bettina M; Duda, Georg N; Checa, Sara
ABSTRACT: Increasing age is associated with a reduced bone regeneration potential and increased risk of morbidities and mortality. A reduced bone formation response to mechanical loading has been shown with aging, and it remains unknown if the interplay between aging and mechanical stimuli during regeneration is similar to adaptation. We used a combined in vivo/in silico approach to investigate age‐related alterations in the mechanical regulation of bone healing and identified the relative impact of altered cellular function on tissue patterns during the regenerative cascade. To modulate the mechanical environment, femoral osteotomies in adult and elderly mice were stabilized using either a rigid or a semirigid external fixator, and the course of healing was evaluated using histomorphometric and micro‐CT analyses at 7, 14, and 21 days post‐surgery. Computer models were developed to investigate the influence of the local mechanical environment within the callus on tissue formation patterns. The models aimed to identify the key processes at the cellular level that alter the mechanical regulation of healing with aging. Fifteen age‐related biological alterations were investigated on two levels (adult and elderly) with a design of experiments setup. We show a reduced response to changes in fixation stability with age, which could be explained by reduced cellular mechanoresponse, simulated as alteration of the ranges of mechanical stimuli driving mesenchymal stem cell differentiation. Cellular mechanoresponse has been so far widely ignored as a therapeutic target in aged patients. Our data hint to mechanotherapeutics as a potential treatment to enhance bone healing in the elderly. © 2019 American Society for Bone and Mineral Research.